Global warming in Malaysia: Forecasting for the next five years / Muhammad Shahrin Nadzir Zulkifle, Nur Izatul Ain A Malik and Nurul Ain Azizan - Zulkifle, Muhammad Shahrin Nadzir; A Malik, Nur Izatul Ain; Azizan, Nurul Ain (2021)
Global warming affect some human activities such as construction and agriculture. These activities affect the climate change and rising in temperature. In 2050, the world temperature was estimated to increase by 1.5◦C. Hence, this research was conducted to model and forecast monthly temperature of speciﬁc area in Malaysia which are Cameron Highland and Petaling Jaya observed from January 1990 to December 2019. The Seasonal Autoregressive Integrated Moving Average (SARIMA) were applied to the monthly temperature for both places for modeling and forecasting purposes. The best models were evaluated by Akaike’s Information Criterion (AIC), Bayesian’s Information Criterion (BIC) and error measures; Mean Square Error (MSE), Root Mean Square Error (RMSE) and Mean Absolute Percentage Error (MAPE). The model that satisﬁed all criterion is the chosen one. The best model to forecast monthly temperature of Cameron Highland is SARIMA(2,1,1)(3,1,1)12, while for monthly temperature of Petaling, SARIMA(1,0,4)(3,1,2)12 is the most suitable SARIMA model. The result of forecasting show that the monthly temperatures for both places are expected to increase for the next ﬁve years and become an alarm for higher authorities for further actions.